Molecular Epidemiology of Methicillin-Resistant Staphylococcus aureus in Horses, Cats, and Dogs Over a 5-Year Period in France - Haenni, Marisa; Châtre, Pierre; Dupieux-Chabert, Céline; Métayer, Véronique; Bes, Michèle; Madec, Jean-Yves; Laurent, Frédéric (Frontiers in Microbiology, 2017)
Methicillin-resistant Staphylococcus aureus (MRSA) has been reported as a worldwide pathogen in humans and animals including companion animals, i.e. cats, dogs and horses. France lacked a comprehensive nationwide study describing the molecular features of MRSA circulating among companion animals over a large period of time. Here is reported the characterization of 130 non-duplicate clinical MRSA isolates collected from those three animal species from 2010 to 2015 through the French national Resapath network. Characterization of isolates was performed using phenotypic (antimicrobial susceptibility tests (AST)) and molecular (DNA arrays, spa-typing) methods. A horse-specific epidemiology was observed in France with the large dissemination of a unique clone, the CC398 clone harboring a Staphylococcal chromosomal cassette mec (SCCmec) type IV and spa-type t011. It was even the unique clone collected in 2015 whereas the clone CC8 USA500 (SCCmec type IV), classically described in horses, was present until 2014. Contrarily, cats and dogs were mainly infected by human-related MRSA isolates, i.e. clones usually reported in human infections, thus mirroring the human epidemiology in hospitals in France. Isolates belonging to the CC398 clone (SCCmec type IV or V) were also identified in 21.4% of dogs’ and 26.5% of cats’ MRSA isolates. In order to differentiate human-related from CC398 MRSA, tetracycline-resistance (or tet(M) detection) could be useful since this resistance is scarce in human-related strains but constant in CC398 MRSA isolates. In all, our data give a nationwide epidemiological picture of MRSA in companion animals over a 5-year period in France, adding further epidemiological information on the contribution of those animal species to a major public health issue. Considering the wide dissemination of CC398 MRSA isolates and the fact that 11/64 (17.2%) of them presented the Immune Evasion Cluster (IEC) which enhances CC398 capacities to colonize humans, a specific attention should be paid in the coming years to determine the risk associated to the transmission in people in frequent contacts with companion animals. Our data also show that the prevalence of MRSA has likely decreased in cats, dogs and horses between 2012 and 2015 in France. This trend should be monitored in the years to come.